2018
DOI: 10.1523/jneurosci.0716-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Updating Beliefs under Perceived Threat

Abstract: Humans are better at integrating desirable information into their beliefs than undesirable information. This asymmetry poses an evolutionary puzzle, as it can lead to an underestimation of risk and thus failure to take precautionary action. Here, we suggest a mechanism that can speak to this conundrum. In particular, we show that the bias vanishes in response to perceived threat in the environment. We report that an improvement in participants' tendency to incorporate bad news into their beliefs is associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
65
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 51 publications
11
65
0
2
Order By: Relevance
“…ACC has also been implicated amongst other prefrontal sites in tracking reward history (Seo et al, 2007;Bernacchia et al, 2011). This would align with previous neurophysiological work in human learning, which implicates heightened stress states -assayed via electrodermal activity -with closer trialwise tracking of adjustments in information integration (Li et al, 2011), with selective stress-driven sensitivity increases to negative prediction errors, eradicating positive learning biases that emerge under calm conditions when stress levels are normal (Garrett et al, 2018).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…ACC has also been implicated amongst other prefrontal sites in tracking reward history (Seo et al, 2007;Bernacchia et al, 2011). This would align with previous neurophysiological work in human learning, which implicates heightened stress states -assayed via electrodermal activity -with closer trialwise tracking of adjustments in information integration (Li et al, 2011), with selective stress-driven sensitivity increases to negative prediction errors, eradicating positive learning biases that emerge under calm conditions when stress levels are normal (Garrett et al, 2018).…”
Section: Discussionsupporting
confidence: 78%
“…Appraising sequential offers of reward relative to an unknown future opportunity and a time cost requires an optimization policy that draws on a belief about the richness characteristics of the current environment. Across a range of experiments, including reinforcement-learning tasks, belief updating paradigms and prey selection, information integration shows a positive bias Sharot, 2014, 2017;Garrett et al, , 2018Kuzmanovic et al, 2015Kuzmanovic et al, , 2016Eil and Rao, 2011;Korn et al, 2012;Kuzmanovic and Rigoux, 2017;Lefebvre et al, 2017;Garrett and Daw, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second (Asymmetric Model) learned to a different degree from positive vs. negative prediction errors. This feature, which has been observed in a number of other learning scenarios (Eil and Rao, 2011;Sharot, 2014, 2017;Garrett et al, , 2018Korn et al, 2012;Kuzmanovic and Rigoux, 2017;Kuzmanovic et al, 2015Kuzmanovic et al, , 2016Lefebvre et al, 2017;Mobius et al, 2011;Moutsiana et al, 2013Moutsiana et al, , 2015Sharot and Garrett, 2016;Sharot et al, 2011) but not explored in the context of foraging, gave the model the capacity to express learning asymmetries and to predict and capture specific patterns of experience-dependent biases in choices.…”
Section: Introductionmentioning
confidence: 84%
“…For instance, a model that defined an MVT-like threshold from a simple incremental running average of recent events (Constantino and Daw, 2015) would treat either direction of change symmetrically. We hypothesized, however, that the difference could arise from asymmetric learning, as has been studied in other decision domains (Eil and Rao, 2011;Sharot, 2014, 2017;Garrett et al, , 2018Korn et al, 2012;Kuzmanovic and Rigoux, 2017;Kuzmanovic et al, 2015Kuzmanovic et al, , 2016Lefebvre et al, 2017): individuals changing their subjective estimates of the environment's reward rate differentially depending whether the update was in a positive or negative direction. To formally test this, we adapted a computational model (Constantino and Daw, 2015) to capture how participants maintained ongoing estimates of the environments reward rate during the task and tested whether endowing this model with the capacity to shift estimates up and down at different rates depending on whether the information received suggested that the environment was improving (as would be the case when transitioning from poor to rich) versus deteriorating (as would be the case when transitioning from rich to poor) could account for the relative hesitance of participants to change choices when the environment became worse.…”
Section: Figurementioning
confidence: 99%